2015
DOI: 10.1016/j.mmcr.2015.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Trichosporon faecale invasive infection in a patient with severe aplastic anemia: Efficacy of voriconazole and liposomal amphotericin B before neutrophil recovery

Abstract: We report a case of a 51-year old man with a severe aplastic anemia who developed an invasive trichosporonosis to Trichosporon faecale with fungemia and skin lesions during severe neutropenia. The treatment was successful before neutrophil recovery with a combination of voriconazole and liposomal amphotericin B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…For comparison analysis, the cases were clustered according to the main underlying disease, e.g., homeopathy ( n = 79; Grauer et al, 1994 ; Higgins et al, 1994 ; Hsiao et al, 1994 ; Nasu et al, 1994 ; Hung et al, 1995 ; Spánik et al, 1995 ; Itoh et al, 1996 ; Fanci et al, 1997 ; Kataoka-Nishimura et al, 1998 ; Sklair-Levy et al, 1998 ; Krcmery et al, 1999 ; Takamura et al, 1999 ; Erer et al, 2000 ; Kim et al, 2001 ; Moretti-Branchini et al, 2001 ; Fournier et al, 2002 ; Hadley et al, 2002 ; Meyer et al, 2002 ; Chang et al, 2003 ; Marty et al, 2003 ; Bassetti et al, 2004 ; Chowdhary et al, 2004 ; Viscomi et al, 2004 ; Antachopoulos et al, 2005 ; Chan-Tack, 2005 ; Akagi et al, 2006 ; Ghiasian et al, 2006 ; Kendirli et al, 2006 ; Koyanagi et al, 2006 ; Matsue et al, 2006 ; Meguro-Hashimoto et al, 2006 ; Rodrigues et al, 2006 ; Hara et al, 2007 ; Miura et al, 2007 ; Rieger et al, 2007 ; Bayramoglu et al, 2008 ; Hosoki et al, 2008 ; Thibeault et al, 2008 ; Tsuji et al, 2008 ; Fekkar et al, 2009 ; Walia et al, 2009 ; Gabriel et al, 2011 ; Kudo et al, 2011 ; Hosokawa et al, 2012 ; Menezes et al, 2012 ; Chen et al, 2014 ; Issarachaikul et al, 2014 ; Karapinar et al, 2014 ; Capoor et al, 2015 ; Odero et al, 2015 ; Pérard et al, 2015 ; Tanyildiz et al, 2015 ), other immunodeficiency conditions ( n = 41; Canales et al, 1998 ; Lascaux et al, 1998 ; Anuradha et al, 2000 ; Piwoz et al,…”
Section: Resultsunclassified
“…For comparison analysis, the cases were clustered according to the main underlying disease, e.g., homeopathy ( n = 79; Grauer et al, 1994 ; Higgins et al, 1994 ; Hsiao et al, 1994 ; Nasu et al, 1994 ; Hung et al, 1995 ; Spánik et al, 1995 ; Itoh et al, 1996 ; Fanci et al, 1997 ; Kataoka-Nishimura et al, 1998 ; Sklair-Levy et al, 1998 ; Krcmery et al, 1999 ; Takamura et al, 1999 ; Erer et al, 2000 ; Kim et al, 2001 ; Moretti-Branchini et al, 2001 ; Fournier et al, 2002 ; Hadley et al, 2002 ; Meyer et al, 2002 ; Chang et al, 2003 ; Marty et al, 2003 ; Bassetti et al, 2004 ; Chowdhary et al, 2004 ; Viscomi et al, 2004 ; Antachopoulos et al, 2005 ; Chan-Tack, 2005 ; Akagi et al, 2006 ; Ghiasian et al, 2006 ; Kendirli et al, 2006 ; Koyanagi et al, 2006 ; Matsue et al, 2006 ; Meguro-Hashimoto et al, 2006 ; Rodrigues et al, 2006 ; Hara et al, 2007 ; Miura et al, 2007 ; Rieger et al, 2007 ; Bayramoglu et al, 2008 ; Hosoki et al, 2008 ; Thibeault et al, 2008 ; Tsuji et al, 2008 ; Fekkar et al, 2009 ; Walia et al, 2009 ; Gabriel et al, 2011 ; Kudo et al, 2011 ; Hosokawa et al, 2012 ; Menezes et al, 2012 ; Chen et al, 2014 ; Issarachaikul et al, 2014 ; Karapinar et al, 2014 ; Capoor et al, 2015 ; Odero et al, 2015 ; Pérard et al, 2015 ; Tanyildiz et al, 2015 ), other immunodeficiency conditions ( n = 41; Canales et al, 1998 ; Lascaux et al, 1998 ; Anuradha et al, 2000 ; Piwoz et al,…”
Section: Resultsunclassified
“…They have been involved in a variety of opportunistic infections and have been recognised as emerging fungal pathogens in immunocompromised hosts . Studies also indicated that T. asahii , T. asteroids , T. cutaneum , T. faecale , T. inkin , T. mucoides or T. ovoides are involved in hypersensitivity pneumonitis, pulmonary infections and superficial infections, sinusitis, fungaemia, in HIV patients, a bone marrow transplant recipient, a solid organ transplant recipient and in a patient with severe aplastic anaemia . Members of the genus Trichosporon have occasionally been implicated as nail pathogens and in subcutaneous infections .…”
Section: Resultsmentioning
confidence: 99%
“…7,30,31 Studies also indicated that T. asahii, T. asteroids, T. cutaneum, T. faecale, T. inkin, T. mucoides or T. ovoides are involved in hypersensitivity pneumonitis, pulmonary infections and superficial infections, 32,33 sinusitis, 34 fungaemia, [35][36][37] in HIV patients, 38 a bone marrow transplant recipient, 39 a solid organ transplant recipient 40 and in a patient with severe aplastic anaemia. 41 Members of the genus Trichosporon have occasionally been implicated as nail pathogens [42][43][44] and in subcutaneous infections. 45 Recently, T. dohaense, a newly described species by Taj-Aldeen et al [15] was isolated three times from cutaneous sites (tinea pedis, onychomycosis and an infected catheter site) in Doha, Qatar.…”
Section: Implications Of the Species Isolatedmentioning
confidence: 99%
“…In the present study, of the 13 potentially useful yeast isolates identified, Y. lipolytica (N15) was selected for further evaluation because strains I27, Y4 and I41 are Trichosporon spp., and some yeasts in this genus have been reported as human pathogens. For instance, T. asahii caused urinary tract infection in immunocompetent patients, and T. faecale caused invasive trichosporonosis in an aplastic anaemia patient (Khan, Sahni, Basu, & Haleem, ; Pérard et al, ). However, Y. lipolytica has been reported to improve the survival and growth of the pearl oyster ( P. mazatlanica ) (Aguilar‐Macias, Ojeda‐Ramirez, Campa‐Cordova, & Saucedo, ).…”
Section: Discussionmentioning
confidence: 99%